Intercorporeal Construction of We-Ness in Classroom Interaction - Heinonen Pilvi; Tainio Liisa (Springer Netherlands, 2025)
Drawing on multimodal conversation analysis as a method, this article explores the role of embodiment and tactility in negotiating peer relations in classroom interaction. We aim at discussing how social relations between peers are locally constructed and negotiated through embodied, tactile-haptic, and spatial practices during classroom activities. The focus of the empirical analysis is on how students sequentially co-construct specific peer-to-peer touch type—sustained leaning touch—as well as how embodied two-student formations, synchronization of bodily movements and negotiation of personal space serves as displaying social bonding and balancing between students’ dual role orientation. Our findings suggest that intercorporeal construction of we-ness—including exclusive and inclusive practices in relation to peer groups—is based on students’ embodied orientations during leaning touch as well as re-organized embodied choreographies, participation frameworks and spatial arrangements. Our empirical analysis on tactility, embodied consciousness and incorporeal compresence has its basis in a phenomenologically rooted understanding of intercorporeality, and therefore our article aims at building bridges between phenomenological understanding and conceptualization and detailed empirical analysis of clearly observable interactional phenomena.